2017
DOI: 10.3892/or.2017.5761
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of A disintegrin and metalloprotease 10 promotes tumor proliferation, migration and poor prognosis in hypopharyngeal squamous cell carcinoma

Abstract: The aim of this study was to determine the effect of A disintegrin and metalloprotease 10 (ADAM10) protein expression on the progression, migration and prognosis of hypopharyngeal squamous cell carcinoma (HSCC). Immunohistochemistry and western blot analysis were performed to detect ADAM10 expression in human HSCC specimens. Cell Counting Kit-8 (CCK-8) assay, flow cytometry analysis and wound-healing assay were employed to investigate the effects of ADAM10 knockdown (ADAM10-RNAi) on major oncogenic properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Revealing studies have suggested the potential role of ADAM10 in cell migration and metastasis in various cancers including HCC. In hypopharyngeal squamous cell carcinoma (HSCC), high expression of ADAM10 was suggested to increase epithelial-mesenchymal transition (EMT) regulation, and promote tumor cell migration and infiltration 23 . In human esophageal squamous cell carcinoma (ESCC), active ADAM10 was suggested to promote the carcinogenesis, invasion, metastasis, and proliferation of ESCC and control invasion and metastasis through shedding E-cadherin activity 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Revealing studies have suggested the potential role of ADAM10 in cell migration and metastasis in various cancers including HCC. In hypopharyngeal squamous cell carcinoma (HSCC), high expression of ADAM10 was suggested to increase epithelial-mesenchymal transition (EMT) regulation, and promote tumor cell migration and infiltration 23 . In human esophageal squamous cell carcinoma (ESCC), active ADAM10 was suggested to promote the carcinogenesis, invasion, metastasis, and proliferation of ESCC and control invasion and metastasis through shedding E-cadherin activity 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A further study illustrated that miR-489-3p directly bound to ADAM10 3'UTR, suggesting that miR-489-3p might block the function of ADAM10. ADAM10 overexpression was reported to trigger tumor cell proliferation and migration and result in a poor prognosis of HSCC [33]. ADAM10 was also identified to be a target of miR-140-5p, and ADAM10 knockdown suppressed HSCC cell proliferation, migration, and invasion [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation was analyzed by a CCK-8 kit (KGA317, Beyotime Institute of Biotechnology) [21]. Briefly, cells (4 × 10 3 per well) were seeded into 96-well plates and each group contained five replicates.…”
Section: Cell Counting Kit-8 (Cck-8) Assaymentioning
confidence: 99%